PENGARUH SUHU YANG BERBEDA TERHADAP KELANGSUNGAN HIDUP (SURVIVAL RATE) LARVA IKAN KARPER MAJALAYA (CYPRINUS SP): Influence of Different Temperature to Continuity of Life ( Survival of Rate) Fish Carp of Majalaya ( Cyprinus Sp) - Lalu Makrullah; Aryani Rahmawati; Luh Gede Sumahiradewi; Lalu Samsul Rizal (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2023)
Intention of this research that is to know influence of different temperature to continuity of carp fish life of majalaya (Cyprinus sp) and to know best temperature to continuity of carp fish life of majalaya. Method which is used in this research is method " eksperiment" that is an research method by performing a some unit activity of attempt to see an result of which is gone domicile and affirm relation I come from among variable perceived or investigated. Result of research of gone of is continuity of highest life that is obtained at treatment of B2 (temperature 28oC) mean equal to 88%, followed by treatment of A1 (temperature 26oC) equal to 85%, treatment of C3 (temperature 30oC) equal to 83,33%, and continuity of mean life of down at treatment of D4 (temperature 32oC) that is equal to 81%